If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+0)(x-3)=0
We add all the numbers together, and all the variables
(+x)(x-3)=0
We multiply parentheses ..
(+x^2-3x)=0
We get rid of parentheses
x^2-3x=0
a = 1; b = -3; c = 0;
Δ = b2-4ac
Δ = -32-4·1·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{9}=3$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-3}{2*1}=\frac{0}{2} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+3}{2*1}=\frac{6}{2} =3 $
| 2x(x^2+4)=1 | | -x+7=7 | | 3(x+8)-9=-3x-12 | | x÷8-2=4 | | Y=1.19c+56 | | f(-3)=5(-3^2)-7(-3)+1 | | 2(x-4)=74 | | 6y=10Y= | | (p-1)(2p-3)=0 | | 25x^2-4x+16=0 | | 8x^2-49x-49=0 | | (3y+2)+3y=127 | | .5a+6.2=12 | | (x+7)(8x+-7)=0 | | 4=2^x | | -16*t^2+14t+12=0 | | 6x+4+8x-16=180 | | 2(4t-6)=21t+7 | | -15=x-81= | | 3(2x-5)=2(3x-1)+1x | | 16t^2-50t+27=0 | | 3x−2.4=9.6, | | 2(4t-6)=19t+8 | | 3+2(x+4)=4x-1 | | x-4-3x=6x=x=25 | | 4(x-2)^2=64 | | 2(x-3)-3=5x-3(4+x) | | 3w^+7w=6 | | x2+6x+10=37 | | 2x(4x+-1)=4+2x | | -5v+3=-37 | | 4=2.3^x |